Mitoxantrone‐Induced Cardiotoxicity in Acute Myeloid Leukemia—A Velocity Vector Imaging Analysis. Issue 8 (24th April 2016) - Shaikh, Amir Y.; Suryadevara, Sourabh; Tripathi, Abhishek; Ahmed, Mohamed; Kane, Jennifer L.; Escobar, Jorge; Cerny, Jan; Nath, Rajneesh; McManus, David D.; Shih, Jeffrey; McGuiness, Matthew E.; Tighe, Dennis A.; et al.
Abstract : Background: The purpose of this investigation was to: (1) determine incidence and predictors of mitoxantrone‐induced early cardiotoxicity and (2) study left ventricular mechanics before and after receiving mitoxantrone. Method and Results: We retrospectively analyzed 80 subjects diagnosed with acute myeloid leukemia (AML) who underwent chemotherapy with bolus high‐dose mitoxantrone. Echocardiographic measurements were taken at baseline and at a median interval of 55 days after receiving mitoxantrone. Thirty‐five (44%) of the patients developed clinically defined early cardiotoxicity, 29 (36%) of which developed heart failure. There was a significant decrease in the ejection fraction (EF) not only in the cardiotoxicity group (17.6 ± 14.8%, P < 0.001) but also in the noncardiotoxicity group (5.3 ± 8.4%, P < 0.001). Decrease in global longitudinal strain (GLS) (−3.7 ± 4.5, P < 0.001 vs. −2.4 ± 4.3, P = 0.01) and global circumferential strain (GCS) (−5.6 ± 9, P = 0.003 vs. −5.3 ± 8.7, P < 0.001) was significant in both the cardiotoxicity and noncardiotoxicity group, respectively. A multivariate model including baseline left ventricular end‐systolic diameter, baseline pre‐E/A ratio, and baseline pre‐E/e′ ratio was found to be the best‐fitted model for prediction of mitoxantrone‐induced early clinical cardiotoxicity. Conclusion: High‐dose mitoxantrone therapy is associated with an excellent remission rate but with a significantly increased risk of clinical and subclinical early cardiotoxicity and heart failure. Mitoxantrone‐induced systolic dysfunction is evident from reduction in EF, increase in Tei index, and significant reduction in GLS and GCS. Baseline impaired ventricular relaxation evident from higher E/e′ ratio and lower E/A ratio independently predicts increased risk of mitoxantrone‐induced early cardiotoxicity.